Council cottages and community in inter-war Britain: a study of class, culture,politics and place - Bayliss, Darrin (1998)
PhDThis thesis makes a contribution to the debates surrounding the idea of community on the cottage council estates of inter-war Britain. It questions the conventional wisdom that community was lacking upon these estates. Recognising the problematic nature of the notion of community, this thesis overcomes the confusion inherent in the term when it is used to describe social structures by viewing community instead as a structure of meaning, as a discursive rather than material reality. This guides my examination of community on the estates. Rather than there being no community, it is argued that there were at least three different discourses of community, and what is important is the relationships between them. Chapter One discusses the contexts in which these estates were built, and then sets out the ways in which community is understood in this thesis. Chapter Two explains the methodology that was used, a combination of archival and oral histoiy. In Chapter Three Roehampton and Watling - the two estates this research focuses upon - are described in order to provide the contextual setting for my interpretation of the discourses of community that were present there. Chapter Four is concerned with community from the viewpoint of the residents who lived on the estates. Chapter Five considers discourses of community from the point of view of the tenants' and residents' associations that developed upon Roehampton and Watling. Chapter Six explores the discourse of community that was promoted on the estates by the Community Association movement. Overall the thesis argues that the discourses of community on inter-war housing estates have to be understood in terms of the occupational structures, cultures and politics of these estates